Problems of Wage Regulation in the Russian Far North and Similar Localities - Lishchuk, Elena Nikolaevna; Kapelyuk, Sergey Dmitrievich (Economy of Regions, 2020)
The increase of minimum wage in 2018 in Russia turned out to be the most pronounced in regions of the Far North and similar localities due to the exclusion of regional compensation payments and Northern allowances from the minimum wage. We are interested in both studying the effects of the minimum wage’s increase and assessing its value’s compliance. The article suggests a new approach to achieving these objectives based on the number of workers’ complaints to the State Labour Inspectorate. We developed and applied an econometric model to reveal the connection between the rate of compensation payments in a region and the number of complaints regarding the problem that “the employer pays less than the law requires”. As the study’s information base, we used the data gathered from an online dataset of the Federal Service for Labour and Employment, Federal State Statistics Service, and the professional database “Ruslana”. We discovered that in 2018, the number of complaints on the considered topic in the North regions was 2.5 times higher than in other regions. An increase in the value of regional compensation payments is associated with an increase in the number of complaints. The largest number of complaints came from employees of small enterprises, budgetary institutions, and firms experiencing financial difficulties. The legal authorities may use suggested recommendations regarding the legislation of the status of regional compensation payments and Northern allowances in the process of determining the minimum wage. We recommend the employers to use the checklists that allow minimizing the risks of consequences of labour law’s violations in the Far North and similar localities.